Analisis Kriteria Seorang Pelayan Tuhan di Era Transisi Berdasarkan 2 Timotius 4:6-7 - Adolf Butarbutar (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this paper is to analyze the criteria of a faithful servant of God in the transitional era based on 2 Timothy 4:6-7. The approach used is descriptive qualitative method by collecting data through the Bible and other literature such as journals, books and documents relevant to the topic discussed. A wrong understanding of choosing a way of life as a servant of God can have a negative impact that can lead to a high level of depression which can result in a servant deciding to stop serving God's work in the midst of turmoil and changes that continue to occur in this transitional era. As a result, the criteria for God's servants who are needed in a transitional or changing era are servants who have the ability to be able to remain faithful in ministry until the end of their lives: namely the ability to think critically, communicatively, creatively and innovatively. In conclusion, whenever, in any condition and wherever one is, a servant of God is required to keep the criteria of loyalty to God and the work of service until the end of his life.